THE CHOICE OF FOREIGN LEGAL TRANSPLANTS POLICY IN REGULATING INDONESIAN COPYRIGHT LAW: BETWEEN STANDARDIZATION AND COAGULATION - O.K. Saidin (Fakultas Hukum Universitas Gadjah Mada, 2015)
Any legal development shall be coming along with the development of civilization. Building the whole society to be more civilized–to live by the standardized customs, religions and in accordance with any cultural values to be well-institutionalized normatively in the life of people. The standardization of law in normative form is to adopt legal policy of law transplantation deriving from foreign tradition and culture to be transplanted into model of law in home country. Quite often, such legal transplantation is not effective to be implemented. In the case of Indonesian copyright, the law which was before standardized eventually becomes coagulated. Pembangunan hukum sebenarnya adalah pembangunan peradaban. Membangun masyarakat agar bisa hidup beradab. Hidup dengan standar adat istiadat, kebiasaan, moral, religius dan nilai-nilai kultur yang dibakukan secara normatif. Pembakuan hukum dalam bentuk normatif dengan memilih politik hukum transplantasi adalah memilih model hukum yang berasal dari kultur atau budaya asing untuk dicangkokkan menjadi model hukum di negeri sendiri. Kerap kali hukum hasil pencangkokkan itu tak cukup efektif untuk diterapkan. Dalam kasus transplantasi undang-undang hak cipta Indonesia, hukum yang semula dibakukan akhirnya menjadi hukum yang dibekukan.